Surface flashover patterns of GIS basin insulator under impulse voltage. (December 2021) - Liu, Lin; Zheng, Yao; Hao, Yanpeng; Zhang, Qiaogen; Li, Xiaoang; Chen, Lingcheng; Li, Licheng
Highlights: There are three types of surface flashover according to its initial position: surface of shielding electrode, triple junction and the surface of insulator. The causation of surface flashover could be judged by the ablation points and trace morphology. Surface flashover caused by metal particle on insulator suface may be mistaken as caused by triple junction for the arc trace may not cross it. The obvious black carbonization and the invisible ablation trace morphology could further help to judge the initated position of surface flashover. Abstract: Basin insulator is an important component of SF6 gas insulated switchgear (GIS), and its fault is also one of the major causes of GIS equipment failure. Due to the large capacity of high voltage power system, the faulty basin insulators are generally burned severely by the high energy arc, so the fault diagnosis is very difficult. In this paper, the surface flashover pictures of several full-scaled GIS basin insulators under impulse voltage are collected, and the morphology features of flashover traces initiating from different positions are summarized. As a result, the surface flashover patterns are divided into three types: 1) surface of shielding electrode initiated flashover, 2) triple junction initiated flashover and 3) surface of insulator initiated flashover. The inception and development process of flashover are also summarized. Besides, the diagnosis method of discharge inception position is proposed. Firstly, check the ablation points at high voltage terminal. If there is a ablation point on the surface of shielding electrode, the flashover initiates from there. If there is only ablation point at the triple junction, the inception position depends on the flashover trace morphology: when the flashover trace disperses in a single direction towards grounding electrode or high voltage electrode, the flashover initiates from the opposite triple junction; when the flashover trace disperses towards both electrodes, the flashover initiates from the insulator surface. The dispersion direction could be directly distinguished from the black carbonized dendritic traces, or from the "white dendritic traces" with the auxiliary methods. The conclusions could help the substation maintenance staff do the root cause analysis of the surface flashover, and assist the researchers in the structural optimization design of basin insulator.